Board Size and Financial Performance as a Driver for Social Innovation: Evidence from Italian Local State-Owned Enterprises - Cristina Cersosimo; Nathalie Colasanti (Administrative Sciences, 2025)
This article investigates the effects of board size on financial performance and the indirect effects of this relationship on social innovation (SI). An Ordinary Least Squares (OLS) model was run on a stratified random sample of 111 Italian local state-owned enterprises (SOEs). Data refer to the year 2018. Many other prior studies have provided empirical evidence on the connection between board size and financial performance, with controversial results. In addition, none of them have investigated the context of local Italian SOEs, and none have linked this relationship with SI. This gap is significant given the growing role of Italian local SOEs in addressing public needs and promoting SI. We discovered that a larger board enhances financial performance in the sample analysed. This result finds its foundations in resource dependence theory, independence theory, and in the work of some agency theorists, and it also supports these theoretical lenses. In addition, in line with arguments on the theory of shared value, we support the view that the positive relationship between board size and financial performance incentivises SI.